Emotion in the Tudor court: literature, history, and Early Modern feeling - Irish, Bradley J. (Rethinking the early modern, 2018)
The disgusting Cardinal Thomas Wolsey -- The envious Earl of Surrey -- The rejected Earl of Leicester, the rejected Sir Philip Sidney -- The dreading, dreadful Earl of Essex